1996
DOI: 10.1073/pnas.93.23.12840
|View full text |Cite
|
Sign up to set email alerts
|

Repair of thalassemic human β-globin mRNA in mammalian cells by antisense oligonucleotides

Abstract: In one form of ␤-thalassemia, a genetic blood disorder, a mutation in intron 2 of the ␤-globin gene (IVS2-654) causes aberrant splicing of ␤-globin pre-mRNA and, consequently, ␤-globin deficiency. Treatment of mammalian cells stably expressing the IVS2-654 human ␤-globin gene with antisense oligonucleotides targeted at the aberrant splice sites restored correct splicing in a dose-dependent fashion, generating correct human ␤-globin mRNA and polypeptide. Both products persisted for up to 72 hr posttreatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(164 citation statements)
references
References 22 publications
5
157
0
2
Order By: Relevance
“…To test the in vivo effects of antisense oligonucleotides, HeLa based cell lines stably expressing human thalassemic b-globin genes IVS2-654, -705, and -745 driven by the CMV promoter were generated by cotransfection with plasmids carrying the appropriate globin gene and the neomycin resistance marker+ The stably transfected cells were treated with complexes of Lipofectamine and 17 or 18-mer 29-O-methyl-oligoribonucleoside phosphorothioates (Table 1) targeted to the aberrant splice sites resulting from a given mutation (see Sierakowska et al+, 1996 and Materials and Methods)+ Bennett, 1998)+ This charge ratio was exceeded at 0+4 and 0+6 mM concentration of the oligonucleotide leading to a decrease in the correction of splicing (Fig+ 2, lanes 5 and 6)+ However, the design of this experiment allows for determination of the true maximal effect under given experimental conditions+ The effects are strictly sequence specific since a number of control oligonucleotides such as those with random sequence, mismatch, or targeted to regions of the intron distant from the splicing elements were ineffective (Sierakowska et al+, 1996;Kang et al+, 1998, and data not shown)+ (231) spliced RNAs+ Note that RT-PCR was carried out in the presence of a[ 32 P]-ATP and that the adenosine nucleotide content in the aberrantly spliced product is 1+57 times that of the correctly spliced one+ Thus, the degree of correction is higher than it appears from the autoradiogram (see Materials and Methods)+ Restoration of correct splicing of IVS2-745 pre-mRNA was even more efficient than in the other two mutants+ At 10 nM ON-745 oligonucleotide, only correct b-globin mRNA was detected (Fig+ 4, lane 3)+ Interestingly, although the aberrantly spliced RNA was no longer detectable, the level of b-globin mRNA increased in a dose dependent manner at 30-300 nM ON-745 (Fig+ 4, lanes 5-7)+ A likely interpretation of this result is that the stability of the correct b-globin mRNA is higher than that of its aberrantly spliced 745 counterpart and therefore the product of correct splicing of IVS2-745 premRNA accumulates at a higher steady state level+…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the in vivo effects of antisense oligonucleotides, HeLa based cell lines stably expressing human thalassemic b-globin genes IVS2-654, -705, and -745 driven by the CMV promoter were generated by cotransfection with plasmids carrying the appropriate globin gene and the neomycin resistance marker+ The stably transfected cells were treated with complexes of Lipofectamine and 17 or 18-mer 29-O-methyl-oligoribonucleoside phosphorothioates (Table 1) targeted to the aberrant splice sites resulting from a given mutation (see Sierakowska et al+, 1996 and Materials and Methods)+ Bennett, 1998)+ This charge ratio was exceeded at 0+4 and 0+6 mM concentration of the oligonucleotide leading to a decrease in the correction of splicing (Fig+ 2, lanes 5 and 6)+ However, the design of this experiment allows for determination of the true maximal effect under given experimental conditions+ The effects are strictly sequence specific since a number of control oligonucleotides such as those with random sequence, mismatch, or targeted to regions of the intron distant from the splicing elements were ineffective (Sierakowska et al+, 1996;Kang et al+, 1998, and data not shown)+ (231) spliced RNAs+ Note that RT-PCR was carried out in the presence of a[ 32 P]-ATP and that the adenosine nucleotide content in the aberrantly spliced product is 1+57 times that of the correctly spliced one+ Thus, the degree of correction is higher than it appears from the autoradiogram (see Materials and Methods)+ Restoration of correct splicing of IVS2-745 pre-mRNA was even more efficient than in the other two mutants+ At 10 nM ON-745 oligonucleotide, only correct b-globin mRNA was detected (Fig+ 4, lane 3)+ Interestingly, although the aberrantly spliced RNA was no longer detectable, the level of b-globin mRNA increased in a dose dependent manner at 30-300 nM ON-745 (Fig+ 4, lanes 5-7)+ A likely interpretation of this result is that the stability of the correct b-globin mRNA is higher than that of its aberrantly spliced 745 counterpart and therefore the product of correct splicing of IVS2-745 premRNA accumulates at a higher steady state level+…”
Section: Resultsmentioning
confidence: 99%
“…Quantitation of the results shown in Figures 2-4 and of additional experiments and the linear regression analysis of the oligonucleotide concentration shows that the EC 50 of the oligonucleotides targeted to the three aberrant 59 splice sites differs by up to 115-fold (Table 2 and Materials and Methods)+ Several lines of evidence indicate that the difference in the sensitivity of the targeted splice sites is an intrinsic property of the spliced pre-mRNAs and is not due to variations of the oligonucleotides and/or the cell lines+ The levels of aberrantly spliced RNAs decrease significantly in the order IVS2-654, -705, -745 (compare lane 1 in Figs+ 2, 3A, and 4) suggesting that expression of the thalassemic genes could be different in the three cell lines+ Consequently, the ratio of the oligonucleotide to the premRNA target could be much higher in IVS2-705 and -745 than in IVS2-654 cells+ This higher ratio would favor hybridization of the oligonucleotides, promoting correction of splicing+ However, the level of b-globin pre-mRNA, assayed by RT-PCR of total cellular RNA, was found to be lowest in the IVS2-654 cell line, intermediate in -705, and the highest in -745 (Fig+ 5,upper panel,lanes,2,3,and 5; the construct IVS2-654con, lane 4, is discussed in the subsequent section)+ A control PCR reaction, with the reverse transcription step omitted, shows that these results are not due to genomic DNA, a possible contaminant of the RNA preparation (Fig+ 5, lower panel)+ This indicates that correction of splicing of IVS2-654 pre-mRNA was the least efficient in spite of the most favorable ratio of the antisense oligonucleotide to its target (see also Discussion)+ Although the 18-mer oligonucleotides ON-654, -705, and -745 differ in sequence, their hybridization potential, as reflected by their GC content and Tm values (Table 1), is identical and hence unlikely to be responsible for the observed differences in correction of splicing+ The secondary and/or tertiary structure of the pre-mRNAs around the targeted splice sites is also unlikely to differentially affect access of the oligonucle- otides+ Computer analysis (Jaeger et al+, 1989; Wisconsin Package, V+ 9+1) of the folding of IVS2-654, -705, and -745 introns, which vary only by single point mutations, did not reveal any obvious differences (not shown)+ Splicing of thalassemic pre-mRNA in two different clones of HeLa IVS2-654 and three different clones of HeLa-705 cells showed similar differences in sensitivity to ON-654 and ON-705 nucleotides, respectively, as well as to the 39-cryptic splice site oligonucleotide common to all three mutants (data not shown, see also below)+ These differences were retained in two independent clones of IVS2-654 and two of IVS2-705 cell lines based on erythroid, K-562 cells (L+ Gorman and R+ Kole, unpubl+)+ Likewise, the differences in sensitivity between IVS2-654, -705, and -745 were observed in cells transfected with U7 snRNAs targeted to the aberrant splice sites (Gorman et al+, 1998 and unpubl+ data)+ Furthermore, 3T3 IVS2-654 cells (Sierakowska et al+, 1996) showed sensitivity to ON-654 characteristic of the HeLa and K562 IVS2-654 cells+ These observations exclude the possibility that the selected clonal cell lines might have differed in their abil...…”
Section: Analysis Of Ivs2 Mutants and Oligonucleotidesmentioning
confidence: 95%
“…ISIS 16009 hybridizes to a region of the Bcl-X gene that is present in Bcl-x L and the alternative splice product, Bcl-x s . Recently, experimental evidence has shown that antisense oligonucleotides function by hybridizing to pre-mRNA in the nucleus (Sierakowska et al, 1996;Condon and Bennett, 1996). Thus, because the same gene encodes Bcl-x L and Bcl-x S , it is impossible to design an oligonucleotide that selectively targets Bcl-x L .…”
Section: Selection Of a Bcl-x L Antisense Oligonucleotide Inhibitormentioning
confidence: 99%
“…24 These cells were sequentially transduced with the pLVT-U7 lentiviral vector (here carrying the U7-Do3-Ex1 construct) and the tTR-KRAB vector. The aberrant exon inclusion level was 100% in the absence of any treatment, whereas the single transduction with the U7-Do3-Ex1 vector led to a full splicing correction with 100% exon skipping ( Figure 5).…”
Section: Characterization Of the Regulation Systemmentioning
confidence: 99%
“…14,23 HeLa-705 cells stably express the human b-globin gene carrying the IVS2-705 mutation. 24 Conditions for cell culture, DNA transfections, lentiviral vector production in 293-T cells, titration on HeLa cells and transduction have been described. 8,14 Modifications used here were that HS2 cells were kept under constant selection pressure with 500 mg ml À1 G418 (Invitrogen, Carlsbad, CA, USA) and that their media contained 10% tetracycline-free foetal calf serum (BioConcept, Allschwil, Switzerland).…”
Section: Cell Culturementioning
confidence: 99%